Vitamin K Status Based on K1, MK-4, MK-7, and Undercarboxylated Prothrombin Levels in Adolescent and Adult Patients with Cystic Fibrosis: A Cross-Sectional Study - Krzyżanowska-Jankowska, Patrycja; Nowak, Jan; Karaźniewicz-Łada, Marta; Jamka, Małgorzata; Klapkova, Eva; Kurek, Szymon; Drzymała-Czyż, Sławomira; Lisowska, Aleksandra; Wojsyk-Banaszak, Irena; Skorupa, Wojciech; Szydłowski, Jarosław; Prusa, Richard; et al. (Nutrients, 2024)
The available evidence on vitamin K status in cystic fibrosis (CF) is scarce, lacking data on vitamin K2 (menaquinones-MK). Therefore, we assessed vitamin K1, MK-4 and MK-7 concentrations (LC-MS/MS) in 63 pancreatic insufficient and modulator naïve CF patients, and compared to 61 healthy subjects (HS). Vitamin K1 levels did not differ between studied groups. MK-4 concentrations were higher (median <1st-3rd quartile>: 0.778 <0.589-1.086> vs. 0.349 <0.256-0.469>, p < 0.0001) and MK-7 levels lower (0.150 <0.094-0.259> vs. 0.231 <0.191-0.315>, p = 0.0007) in CF patients than in HS. MK-7 concentrations were higher in CF patients receiving K1 and MK-7 supplementation than in those receiving vitamin K1 alone or no supplementation. Moreover, vitamin K1 concentrations depended on the supplementation regime. Based on multivariate logistic regression analysis, we have found that MK-7 supplementation dose has been the only predictive factor for MK-7 levels. In conclusion, vitamin K1 levels in CF are low if not currently supplemented. MK-4 concentrations in CF patients supplemented with large doses of vitamin K1 are higher than in HS. MK-7 levels in CF subjects not receiving MK-7 supplementation, with no regard to vitamin K1 supplementation, are low. There do not seem to be any good clinical predictive factors for vitamin K status.
Keywords: Young Adult; nutriční stav; Cross-Sectional Studies; vitamin K 1; vitamin K; nedostatek vitaminu K; Male; liquid chromatography; vitamin K1; vitamin K 2; cystic fibrosis; mladý dospělý; Vitamin K 1; Adolescent; Vitamin K 2; Cystic Fibrosis; Adult; dospělí; vitamin K2; mužské pohlaví; gastroenterology; pancreatic insufficiency; potravní doplňky; mladiství; Dietary Supplements; protrombin; lidé; cystická fibróza; ženské pohlaví; Vitamin K; Humans; Nutritional Status; průřezové studie; Prothrombin; Female; Vitamin K Deficiency